Conditional cash transfer in Egypt: the need for proper financial and administrative controls - Badawy, Ahmed Fathy (AUC Knowledge Fountain, 2012)
Conditional cash transfer (CCT) programs, as one of the most efficient social protection programs, use large amount of public resources. Such programs are prone to leakage of public resources due to risks from error, fraud, and corruption. Countries in Latin America have implemented CCT programs since the early 1980's and they have experienced leakages from error, fraud, and corruption (EFC) which requires use of mechanisms and a control system to tackle the risks of EFC. These mechanisms have been introduced in the World Bank toolkit on tackling error, fraud, and corruption. The recommended strategies to mitigate EFC address risks through three main strategies: prevention, detection strategies, and deterrence. This study answers the main research question of what guidance does Egyptian and global experience provide as to what constitutes a proper control system for the implementation of conditional cash transfer programs to prevent error, fraud, and corruption? It provides a vision of what proper controls could be useful for implementing CCT in Egypt and other countries that share similar characteristics. This broader perspective of protection mechanisms has been investigated through contacting global experts from different countries and local social inspectors who worked in the pilot project in Egypt. This combination takes advantage of global and local experiences recommend what could enable Egypt to have a proper control system to reduce EFC. The study findings demonstrate that Egypt can apply proper administration and financial controls in its CCT program at each of its three main stages: eligibility, compliance, and cash disbursing. Recommended control mechanisms are developed around three building blocks of prevention; detection; and deterrence. Other recommendations are provided for CCT program in Egypt regarding interministerial cooperation, the required political support to CCT for program success, use of computerized systems in the verification processes, and a reconsideration of economic, political, and administrative challenges to CCT programs in Egypt.